Effect of walking in nature on stress levels and performance of taekwondo athletes in the competition period - Boobani, B.; Grants, J.; Litwiniuk, A.; Boge, I.; Glaskova-Kuzmina, T. (Journal of Kinesiology and Exercise Sciences, 2024)
Introduction. Despite its importance for sports, the problem of the interaction of genetic and environmental factors affecting sports results in competitions is still not fully understood. This study aimed to evaluate the effect of walking in nature on stress levels and performance of taekwondo athletes during the competition period.